Charge frustration in a triangular triple quantum dot - Seo, M; Choi, H K; Lee, S-Y; Kim, N; Chung, Y; Sim, H-S; Umansky, V; Mahalu, D (Physical review letters, 2013)
We experimentally investigate the charge (isospin) frustration induced by a geometrical symmetry in a triangular triple quantum dot. We observe the ground-state charge configurations of sixfold degeneracy, the manifestation of the frustration. The frustration results in omnidirectional charge transport, and it is accompanied by nearby nontrivial triple degenerate states in the charge stability diagram. The findings agree with a capacitive interaction model. We also observe unusual transport by the frustration, which might be related to elastic cotunneling and the interference of trajectories through the dot. This work demonstrates a unique way of studying geometrical frustration in a controllable way.